A bibliometric and visual analysis of Parkinson’s disease sleep disorders: articles from 2008 to 2023 - Zhu, Lili; Zhu, Peiyuan; Wang, Juwei; Yan, Kaiwen; Zhao, Sheng; Jiang, Yue; Zhang, Huihe (Frontiers in Psychiatry, 2024)
Objective Sleep disorder is a common non-motor symptom (NMS) of Parkinson’s disease. However, the global research focus on Parkinson’s sleep-related disorders (PDSDs) and future trends remains unclear. Currently, there is no bibliometric analysis of PDSDs. We aim to fill this gap, determine the status of current research, and predict future research hotspots. Methods We selected 1490 publications from the Web of Science Core Collection (WoSCC) database from 2008 to 2023. Based on CiteSpace and VOSviewer, the analysis was performed from the perspectives of the trend in the number of annual publications, countries, institutions, authors, journals, and co-citations. Results A total of 1490 publications from 590 authors from 409 institutions in 77 countries are included. The United States, China, and the United Kingdom are the leading countries. University College London (UCL) is the most prolific institution. Harvard University is the key for cooperation among institutions. Chaudhuri Kallol Ray is a leader in this field. “Movement Disorders” is the most influential journal. “A systematic review of the literature on disorders of sleep and wakefulness in Parkinson’s disease from 2005 to 2015” is the publication with the highest co-citation intensity. Conclusion The total volume of publications on PDSDs is on the rise, entering a relatively high-yield stage in 2020. The COVID-19 pandemic and the emergence of new keywords may be the reasons behind this phenomenon. “quality of life” and “circadian rhythm” are the mainstream topics of PDSD research. Daytime sleepiness is the PDSD subtype that has received the most attention. Sleep quality, biomarkers, and neurodegeneration are likely to become future research hotspots.